The Role of Global Uncertainty in Shaping Trade Flow Relations: A Cross-Country Analysis for Europe - António Afonso; José Alves; Lucas Menescal; Sofia Monteiro (CESifo GmbH, 2024)
We examine the effects of World Uncertainty and Geopolitical Risk on Trade flows for 31 European economies between 1995 and 2023. To do so, we resort to Panel estimation techniques, including OLS and Poisson Pseudo Maximum Likelihood (PPML). Our findings reveal that European nations primarily respond to global uncertainty by concentrating their exports and imports among top trading partners particularly their top 5 highest trading partners. This result is more pronounced when uncertainty is driven by low-income countries. Moreover, there is a stronger relationship between imports and global uncertainty compared to exports. Our study underscores the importance of European economies strategically adapting their export and import approaches in response to these challenges.
Keywords: C23; E44; F14; F41; F62; 330; geopolitical risk; world uncertainty; trade flows; international trade; European economies